Relationship between Principal's Leadership Style and Personality Competence of Kindergarten Teachers in Alak District, Kupang City - Merista Verawati Pit'ay (Universitas Nusa Cendana, 2021)
The purpose of this study was to determine the relationship between the principal's leadership style with the personality competencies of kindergarten teachers in Alak Subdistrict, Kupang City. The research method used in this study was a quantitative research method. This research was conducted in 16 kindergartens in Alak District, Kupang City. The results of this study indicated that there was a strong and positive relationship between the principal's leadership style and the personality competence of kindergarten teachers in Alak Subdistrict, Kupang City. This was shown from the results of the product moment correlation analysis with a correlation coefficient of 0.629 with a significance of 0,000 <0.05.